2014
DOI: 10.1017/s146342361400036x
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and your brain: what do you need to know right now

Abstract: Research links air pollution mostly to respiratory and cardiovascular disease. The effects of air pollution on the central nervous system (CNS) are not broadly recognized. Urban outdoor pollution is a global public health problem particularly severe in megacities and in underdeveloped countries, but large and small cities in the United States and the United Kingom are not spared. Fine and ultrafine particulate matter (UFPM) defined by aerodynamic diameter (<2.5-μm fine particles, PM2.5, and <100-nm UFPM) pose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(109 citation statements)
references
References 133 publications
(192 reference statements)
0
100
1
8
Order By: Relevance
“…Adicionalmente, o sistema de transporte, ao gerar menos resíduos poluidores, diminui os danos ao meio ambiente e à saúde da população, seja essa população usuária ou não de veículos. A comunidade local tem ganhos em saúde e qualidade de vida com a diminuição da poluição, pela diminuição de doenças cardiorrespiratórias, do estresse oxidativo, da inflamação e do envelhecimento precoce (DE PRINS et al, 2014), de doenças neurodegenerativas (CALDERÓN-GARCIDUEÑAS et al, 2015), do câncer de pulmão (FAJERSZTAJN et al, 2013;RAASCHOU-NIELSEN et al, 2013;SAX et al, 2013), entre outras doenças. A melhora na qualidade do ar também é um incentivo à atividade física e a atividades ao ar livre, com ganhos em saúde pública (GRABOW et al, 2012).…”
Section: Resultados Rede De Aspectos E Impactosunclassified
“…Adicionalmente, o sistema de transporte, ao gerar menos resíduos poluidores, diminui os danos ao meio ambiente e à saúde da população, seja essa população usuária ou não de veículos. A comunidade local tem ganhos em saúde e qualidade de vida com a diminuição da poluição, pela diminuição de doenças cardiorrespiratórias, do estresse oxidativo, da inflamação e do envelhecimento precoce (DE PRINS et al, 2014), de doenças neurodegenerativas (CALDERÓN-GARCIDUEÑAS et al, 2015), do câncer de pulmão (FAJERSZTAJN et al, 2013;RAASCHOU-NIELSEN et al, 2013;SAX et al, 2013), entre outras doenças. A melhora na qualidade do ar também é um incentivo à atividade física e a atividades ao ar livre, com ganhos em saúde pública (GRABOW et al, 2012).…”
Section: Resultados Rede De Aspectos E Impactosunclassified
“…PM may irritate airway sensory nerve endings activating vanilloid receptors and causing release of neuropeptides that induce neurogenic inflammation [34]. Chronic pollutant induced epithelial and endothelial injury can lead to systemic inflammation with release of proinflammatory cytokines acting on brain blood vessels via constitutive or induced receptors [35].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Other commonly proposed risk factors for brain cancers include exposure to vinyl chloride, cigarette smoking, alcohol consumption, and environmental toxins. Existing studies, however, have found either no evidence or very weak evidence of a link between these other risk factors and brain cancer (Boffetta et al ; Calderón‐Garcidueñas et al ; Galeone et al ; Vida et al ).…”
Section: Introductionmentioning
confidence: 99%